The effect of self-management support program on patient activation and inner strength in patients with cardiovascular disease. Issue 12 (December 2021) - Gholami, Mohammad; Abdoli Talaei, Arefeh; Tarrahi, Mohammad Javad; Mirzaei Taqi, Fereshteh; Galehdar, Nasrin; Pirinezhad, Pezhman
Highlights: The patient activation levels of people with cardiac disease were increased via a theoretical-based self-management program. The intervention did not have a significant effect on patient's inner strength. Training clinicians in delivering comprehensive self-management programs may hold the key to success. Further clinical trials and multiple measurements are needed to better understand the effects of self-management program. Further studies should be based on management of psychosocial consequences such as inner strength. Abstract: Objective: The aim of the present study was to evaluate the effect of a self-management program on activation and inner strength in patients with cardiovascular diseases (CVDs). Methods: This study assigned 86 patients with CVDs to an experimental and a comparison group utilizing alternate allocation based on a quasi-experimental design. The experimental group participated in a self-management program based on a theoretical framework in three stages, i.e. orientation-recognition, reinforcing-engaging and monitoring-follow-up; whereas the comparison group received routine care. The supportive program was administered through holding five individual face-to-face sessions, providing educational booklets and performing four phone-call follow-ups during three months after discharge. The outcomes were measured using the patient activation measure (PAM) and the inner strength scale (ISS). Results: The between group analysis indicated a statistically-significant difference in the mean score of patient activation (P < 0.001) in the two groups. Nevertheless, there was not a statistically-insignificant difference in the mean score of inner strength between the two groups (P < 0.104). Conclusion: Although a three-month nurse-led self-management support program was found to improve patient activation levels, it was ineffective in promoting inner strength. Practice implications: Psychosocial dynamics should be integrated in providing self-management program by nurses. To promote patient activation, tailored consultations is recommended.